2009
DOI: 10.1021/es901612v
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Operating Parameters on the Biodegradation of Steroid Estrogens and Nonylphenolic Compounds during Biological Wastewater Treatment Processes

Abstract: Abstract. This study investigated operational factors influencing the removal of steroid 18 estrogens and alkylphenolic compounds in two sewage treatment works, one a 19 nitrifying/denitrifying activated sludge plant and the other a nitrifying/denitrifying 20 activated sludge plant with phosphorus removal. Removal efficiencies of >90% for 21 steroid estrogens and for longer chain nonylphenol ethoxylates (NP 4-12 EO) were observed 22 at both works, which had equal sludge ages of 13 days. However, the biological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
49
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(57 citation statements)
references
References 59 publications
8
49
0
Order By: Relevance
“…Results indicate that the average log K d values of target EDCs (except E3) followed the same order as their log K ow values, and were also similar to those reported by Koh et al [31]. On this basis, the distribution proportion of each EDC in the solid phase of return sludge (D) could be readily estimated by the following equation [33]:…”
Section: Variation Of Edcs Concentrations In the Solid Phase Of Retursupporting
confidence: 83%
See 1 more Smart Citation
“…Results indicate that the average log K d values of target EDCs (except E3) followed the same order as their log K ow values, and were also similar to those reported by Koh et al [31]. On this basis, the distribution proportion of each EDC in the solid phase of return sludge (D) could be readily estimated by the following equation [33]:…”
Section: Variation Of Edcs Concentrations In the Solid Phase Of Retursupporting
confidence: 83%
“…Koh et al [31] found that every six-degree drop in sewage temperature could decrease the removal efficiency of E1 sulfate by ca. 20% in a nitrifying/denitrifying process, thus inferring that the low temperature in winter could bring down the activity of arylsulfatase enzymes or reduce the bacteria population containing these enzymes.…”
Section: Variation Of Edcs Concentrations In the Influent And Effluenmentioning
confidence: 99%
“…However, previous studies have shown inconsistent results. Castiglioni et al (2006) reported an enhanced removal of amoxicillin, atenolol, bezafibrate, enalapril and SMX with increasing temperature, whilst Koh et al (2009) found a decrease in temperature from 18 to 12 C did not affect the removal of steroid estrogens and nonylphenolic compounds in the AS process.…”
Section: Seasonal Variation Of Antibiotics Removal In Different Treatmentioning
confidence: 97%
“…Based on observations at full-scale and laboratory scale, researchers have alluded to the importance of redox conditions (Matsui et al, 2000;Joss et al, 2004), hydraulic retention time (HRT) (Svenson et al, 2003) and solids retention time (SRT) (Johnson and Sumpter, 2001;Clara et al, 2005;Koh et al, 2008) as possible unifying parameters to explain the disparity between reported ASP estrogen removal efficiencies. A recent comparative study of two full-scale ASPs operated at nearidentical SRT (Koh et al, 2009) reported similar estrogen removal of > 90%, however, differing specific biomass activities (µg estrogen degraded per kg biomass per day, where Σ EST is the sum of dissolved and adsorbed components of five studied compounds) of 84 and 39 µg ΣEST kg -1 biomass d -1 for the nitrification/denitrification and nitrification/denitrification/phosphorus removal ASP respectively led the authors to conclude that enhancement of estrogen biodegradation could be facilitated by the appropriate microbial population. Particular emphasis has been given to the role of nitrification on the biodegradation of the more recalcitrant EE2; the hypothetical advantage of nitrification has been cited as the augmented cometabolic oxidation observed with other organic compounds in the presence of the ammonium monooxgenase (AMO) enzyme (Vader et al, 2000).…”
Section: Introductionmentioning
confidence: 99%